A genetic locus essential for formate-dependent growth of Bradyrhizobium japonicum. - McClung, C R (1987)
A genetic locus essential for the formate-dependent growth of Bradyrhizobium japonicum was isolated by complementation of ethyl methanesulfonate-induced mutants with a cosmid gene library of B. japonicum DNA. Three related cosmids containing 18.7 kilobase pairs of B. japonicum DNA in common were identified as being able to restore formate-dependent growth capability to mutants lacking either ribulosebisphosphate carboxylase or both ribulosebisphosphate carboxylase and phosphoribulokinase activities. To further localize the complementing gene(s), a series of four deletions spanning a total of 16.1 kilobase pairs were introduced into the B. japonicum chromosome. Each resulting deletion mutant lacked formate dehydrogenase activity and lacked ribulosebisphosphate carboxylase activity and immunologically detectable protein. Three of the four also lacked phosphoribulokinase activity. Two other mutants in which the deletion-bearing recombinant plasmid had integrated into the chromosome also lacked ribulosebisphosphate carboxylase activity and protein and phosphoribulokinase activities. The genetic locus defined by these mutants could contain the structural genes for these enzymes or a regulatory gene(s) controlling their expression or both.